Carvedilol Ameliorates Experimental Atherosclerosis by Regulating Cholesterol Efflux and Exosome Functions - Sy-Jou Chen (International Journal of Molecular Sciences, 2019)
Carvedilol (Cav), a nonselective β-blocker with α1 adrenoceptor blocking effect, has been used as a standard therapy for coronary artery disease. This study investigated the effects of Cav on exosome expression and function, ATP-binding cassette transporter A1 (ABCA1) expression, and cholesterol efflux that are relevant to the process of atherosclerosis. Human monocytic (THP-1) cell line and human hepatic (Huh-7) cells were treated with Cav, and cholesterol efflux was measured. Exosomes from cell culture medium or mice serum were isolated using glycan-coated recognition beads. Low-density lipoprotein receptor knockout (ldlr−/−) mice were fed with high-fat diet and treated with Cav. Cav accentuated cholesterol efflux and enhanced the expressions of ABCA1 protein and mRNA in both THP-1 and Huh-7 cells. In addition, Cav increased expression and function of exosomal ABCA1 in THP-1 macrophage exosomes. The mechanisms were associated with inhibition of nuclear factor-κB (NF-κB) and protein kinase B (Akt). In hypercholesterolemic ldlr−/− mice, Cav enhanced serum exosomal ABCA1 expression and suppressed atherosclerosis by inhibiting lipid deposition and macrophage accumulation. Cav halts atherosclerosis by enhancing cholesterol efflux and increasing ABCA1 expression in macrophages and in exosomes, possibly through NF-κB and Akt signaling, which provides mechanistic insights regarding the beneficial effects of Cav on atherosclerotic cardiovascular disease.